Dampak Kompensasi Terhadap Kinerja dan Kepuasan Kerja Karyawan Selama Masa Covid 19 pada PT XYZ - Ebeneser, Auriand; Safuan, Safuan (Jurnal Manajemen, 2021)
This study discusses the impact of work compensation on employee performance during the Covid 19 pandemic with job satisfaction at PT XYZ. The purpose of this study is to determine the effect of job compensation on employee performance, the effect of job satisfaction on employee performance and the effect on job compensation and job satisfaction on employee performance partially and to see the effect of job compensation and job satisfaction on employee performance simultaneously and for the simultaneous influence. direct and indirect compensation variables on employee performance and compensation. This study used a population of 60 employees as respondents. Data collection uses primary and secondary data. Secondary data using a questionnaire using previous research and linear studies. The analysis technique used is path analysis. Based on the partial test the effect of job compensation on job satisfaction, the effect of compensation on employee performance, the effect of job satisfaction on employee performance partially has a significant effect and the effect of job compensation and job satisfaction on employee performance simultaneously also has a significant effect. Creative Commons Attribution-ShareAlike 4.0 International License.